Ocena skuteczności metod fizykalnych w leczeniu nietrzymania moczu u kobiet - przegląd badań = Evaluation of the efficacy of physical methods in the treatment of urinary incontinence in women - a review of research - Magdalena Weber-Rajek; Irena Bułatowicz; Agnieszka Radzimińska; Katarzyna Strojek; Aleksander Goch; Walery Zukow (Kazimierz Wielki University, 2015)
Weber-Rajek Magdalena, Bułatowicz Irena, Radzimińska Agnieszka, Strojek Katarzyna, Goch Aleksander, Zukow Walery. Ocena skuteczności metod fizykalnych w leczeniu nietrzymania moczu u kobiet - przegląd badań = Evaluation of the efficacy of physical methods in the treatment of urinary incontinence in women - a review of research. Journal of Education, Health and Sport. 2015;5(3):11-34. ISSN 2391-8306. DOI: 10.5281/zenodo.16169 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A11-34 https://pbn.nauka.gov.pl/works/546917 http://dx.doi.org/10.5281/zenodo.16169 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015.   Ocena skuteczności metod fizykalnych w leczeniu nietrzymania moczu u kobiet - przegląd badań Evaluation of the efficacy of physical methods in the treatment of urinary incontinence in women - a review of research   Magdalena Weber-Rajek, Irena Bułatowicz, Agnieszka Radzimińska, Katarzyna Strojek, Aleksander Goch, Walery Zukow   Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy Katedra Fizjoterapii Uniwersytet Kazimierza Wielkiego w Bydgoszczy Wydział Kultury Fizycznej, Zdrowia i Turystyki   dr n. o zdr. Magdalena Weber-Rajek Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy Katedra Fizjoterapii ul. Marii Skłodowskiej-Curie 9, 85-094 Bydgoszcz e-mail: magdawr69@gmail.com   Streszczenie Nietrzymanie moczu definiujemy jako objaw niekontrolowanego wycieku moczu przez cewkę moczową. Schorzenie to stanowi obecnie duży problem zdrowotny i społeczny. Fizjoterapia jest jedną z metod zachowawczego leczenia NTM. Artykuł zawiera przegląd  literatury dotyczącej metod fizykalnych stosowanych w leczeniu NTM w oparciu o artykuły zamieszczone w bazie PubMed oraz Medline.   Summary Urinary incontinence is defined as uncontrolled urine leakage through an urethra. This disease is a major health and social problem. Physiotherapy is one of the methods of conservative treatment of  urinary incontinence. The presented report contains a review of literature concerning physical methods in the treatment of urinary incontinence based of the articles included in PubMed and Medline.   Słowa kluczowe: nietrzymanie moczu, metody fizykalne, elektrostymulacja, stymulacja magnetyczna, biofeedback, terapia wibracyjna całego ciała.   Key words: urinary incontinence, physical methods, electrical stimulation, magnetic stimulation, biofeedback, whole body vibration.